Membangun Jiwa Wirausaha di Usia Muda pada Panti Sosial dan Rumah Tahfiz Al-Qur’an Raudatul Jannah Bukittinggi - Loveana Syaifora; Muhammad Fahrozi; Alief Feisal Haznil (Insan Kreasi Media, 2023)
Entrepreneurship is an innate talent from birth and honed through direct experience in the field, so now the paradigm has shifted. Counseling on Building an Entrepreneurial Spirit at a Young Age at Raudatul Jannah Bukittinggi Qur'anic Social Institution and Tahfiz House is an activity that can provide knowledge and understanding of the importance of business so that we must be able to apply entrepreneurship in the digital era. The method of service activities using socialization and discussion is considered quite appropriate for exploring the problems experienced by marketing, so that they can obtain effective solutions. This outreach activity was also welcomed by the local orphanage The service is carried out at Raudatul Jannah Bukittinggi Qur'anic Social Institution and Tahfiz House. Entrepreneurship has become a scientific discipline that studies values, Participants have a willingness to increase knowledge and understanding of business in entrepreneurship in the digital era which can be seen from the enthusiasm of the participants following this counseling activity. Based on the results of this service activity in the form of counseling, runs smoothly with good teamwork and active participation in this service activity so that the service activities run as expected and hopefully can provide benefits for participants.